2023
DOI: 10.3390/plants12081674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Flavonoid Grain Pigments in Durum Wheat

Abstract: Pigmented cereal grains with high levels of flavonoid compounds have attracted the attention of nutritional science backing the development of functional foods with claimed health benefits. In this study, we report results on the genetic factors controlling grain pigmentation in durum wheat using a segregant population of recombinant inbred lines (RILs) derived from a cross between an Ethiopian purple grain accession and an Italian amber grain cultivar. The RIL population was genotyped by the wheat 25K SNP arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The GWAS of colour variation in rice, twenty-six loci were identified, and at least three candidates involved in the flavonoid metabolic pathway [ 41 ]. In durum wheat, The genetic mapping identified 4 QTLs disclosed the candidate genes Pp-A3 , Pp-B1 , R-A1 , R-B , bHLH ( Myc-1 ) and MYB ( Mpc1 , Myb10 ) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GWAS of colour variation in rice, twenty-six loci were identified, and at least three candidates involved in the flavonoid metabolic pathway [ 41 ]. In durum wheat, The genetic mapping identified 4 QTLs disclosed the candidate genes Pp-A3 , Pp-B1 , R-A1 , R-B , bHLH ( Myc-1 ) and MYB ( Mpc1 , Myb10 ) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that three genotypes carrying homozygous SNPs with a significant effect on the S gene were infected with Oidium neolycopersici , and two had significantly reduced susceptibility to the fungus. Sgaramella et al [ 13 ] used SNP markers to genotype a segregating population of recombinant inbred lines (RILs) obtained by crossing the Ethiopian Purple line of durum wheat with modern durum cultivars. Additionally, the total anthocyanin content (TAC), grain color, and L*, a*, and b* color indexes of whole wheat flour were evaluated in four environments.…”
mentioning
confidence: 99%